Tense and aspect in Bantu - Nurse, Derek (Oxford University Press, 2008)
Derek Nurse looks at variations in the form and function of tense and aspect in Bantu, a branch of Niger-Congo, the world's largest language phylum. His account is based on data from more than 200 Bantu languages and varieties, a representative sample of which is freely available on the publisher's website. - ;Derek Nurse looks at variations in the form and function of tense and aspect in Bantu, a branch of Niger-Congo, the world's largest language phylum. Bantu languages are spoken in central, eastern, and southern sub-Saharan Africa south of a line between Nigeria and Somalia. By current est.